2017
DOI: 10.1111/imm.12869
|View full text |Cite
|
Sign up to set email alerts
|

The immunogenetics of neurological disease

Abstract: Summary Genes encoding antigen‐presenting molecules within the human major histocompatibility complex (MHC) account for the highest component of genetic risk for many neurological diseases, such as multiple sclerosis, neuromyelitis optica, Parkinson's disease, Alzheimer's disease, schizophrenia, myasthenia gravis and amyotrophic lateral sclerosis. Myriad genetic, immunological and environmental factors may contribute to an individual's susceptibility to neurological disease. Here, we review and discuss the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 231 publications
(342 reference statements)
1
49
0
1
Order By: Relevance
“…We also observed that the relevant apaQTLs often map to HLA genes, but that the enrichment is not explained by the HLA locus alone. On the other hand, examples of APA events involving HLA genes have been reported [76,77] and genes encoding antigen-presenting molecules account for the highest fraction of genetic risk for many neurological diseases [78].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the relevant apaQTLs often map to HLA genes, but that the enrichment is not explained by the HLA locus alone. On the other hand, examples of APA events involving HLA genes have been reported [76,77] and genes encoding antigen-presenting molecules account for the highest fraction of genetic risk for many neurological diseases [78].…”
Section: Discussionmentioning
confidence: 99%
“…In Goodpasture's kidney disease, the mechanism of the HLA-DRB1*01 mediated protection has been revealed. The conformation of HLA-DRB1*01 presenting immunodominant autoreactive peptide Soluble HLA II Elevated serum levels Observed in acute phases of multiple sclerosis, rheumatoid arthritis and autoimmune hepatitis, smoking and inflammation in rheumatoid arthritis [59][60][61][62]67 Decreased serum levels Observed in end-stage heart disease, severe sepsis and with melanoma progression [63][64][65] Both susceptible and protective associations HLA-DRB1*15 Diabetes mellitus type I and neurological conditions (see text) 74,86,87 Abbreviations: eQTLs, expression quantitative trait loci; MHC, major histocompatibility complex; SNP, single nucleotide polymorphism.…”
Section: Hla and Disease Associationsmentioning
confidence: 99%
“…In other studies, however, these same alleles/combinations thereof have been established in neurological disorders such as Alzheimer's disease and multiple sclerosis, Parkinson's disease, narcolepsy, and autism (Table 4). [85][86][87] In addition, an increased risk of several inflammatory diseases such as sarcoidosis, especially nonresolving, pediatric-onset inflammatory bowel diseases (both Crohn's disease and ulcerative colitis), adult ulcerative colitis, and systemic lupus erythematosus in European descent, African-American, and Hispanic populations have been associated with DRB1*15:01/15:03 -related haplotypes. 35,38,88,89 Schizophrenia is another chronic neurologic disorder that affects nearly 1% of the world's population.…”
Section: Hla and Disease Associationsmentioning
confidence: 99%
“…Although signals from the major histocompatibility complex region still play the biggest roles among the genetic loci that have been identified for MS susceptibility, a much larger number of HLA alleles and non‐HLA variants in the major histocompatibility complex region have been identified, and recent studies also point out the existence of the complex interactions between MS‐susceptibility alleles in the extended major histocompatibility complex region . As not only HLA class II alleles, but also HLA class I alleles, contribute to MS susceptibility, and HLA class I molecules are the ligands for both T‐cell receptors and killer immunoglobulin‐like receptors, there has been growing interest on killer immunoglobulin‐like receptors analysis …”
Section: Genetics Of Ms Susceptibilitymentioning
confidence: 99%
“…6 As not only HLA class II alleles, but also HLA class I alleles, contribute to MS susceptibility, and HLA class I molecules are the ligands for both T-cell receptors and killer immunoglobulin-like receptors, there has been growing interest on killer immunoglobulin-like receptors analysis. [7][8][9]…”
Section: Genetics Of Ms Susceptibilitymentioning
confidence: 99%